Concurrent progressive multifocal leukoencephalopathy and central nervous system infiltration by multiple myeloma: A case report. (June 2019) - Ruiz-Heredia, Yanira; Sanchez-Vega, Beatriz; Barrio, Santiago; Linares, María; Rapado, Inmaculada; Braggio, Esteban; Stewart, Keith; Folgueira, M Dolores; Ramos, Ana; Collado, Luis; Ruiz, Juan; Toldos, Oscar; et al.
Progressive multifocal leukoencephalopathy rarely occurs in patients with multiple myeloma. Intracranial central nervous system invasion is also an uncommon event in multiple myeloma, occurring in less than 1% of cases. We describe herein an exceptional case of coexisting progressive multifocal leukoencephalopathy and intraparenchymal central nervous system myeloma infiltration. A 73-year-old woman with relapsed multiple myeloma was treated with 15 cycles of lenalidomide and dexamethasone, but therapy had to be stopped because of a hip fracture after a fall. During hospitalization, the patient developed progressive multifocal leukoencephalopathy caused by John Cunningham virus, and a prominent intra-parenchymal CD138-positive infiltrate was detected. VDJ rearrangements of the immunoglobulin heavy chain gene and the mutational profile of plasma cells in bone marrow at the time of diagnosis and in brain biopsy after progression were analyzed by next generation sequencing, showing genetic differences between medullary and extramedullary myeloma cells. The role of long-term treatment with lenalidomide and dexamethasone in the development progressive multifocal leukoencephalopathy or intraparenchymal central nervous system myeloma infiltration remains unknown. However, our results suggest that both events may have arisen as a consequence of treatment-related immunosuppression. Thus, an appropriate clinical approach compatible with the simultaneous treatment of progressive multifocal leukoencephalopathy and multiple myeloma should be developed.